Part II - Towards an OPIM system: results of the OPIM system design simulation and an applicability analysis. (1st January 2002) - Putnik, Goran D.; Avila, Paulo Antonio da Silva
One Product Integrated Manufacturing (OPIM) is a new organisational concept for enterprises, proposed with the objective to satisfy a number of functional requirements for the future enterprise's organisation (for example, requirements for competitiveness, flexibility, quality, efficiency, etc.). The OPIM system is an optimised manufacturing/production system for the purpose of single product manufacturing/production, synthesised over a universal set of primitive resources with a real-time substitutable physical structure where one instantaneous physical structure exists no longer than the lifetime of the product. The OPIM system belongs to the wider concept of the Virtual Enterprise (VE) and it is a special case of a VE. The OPIM system design simulation is presented. The system's applicability domain is identified based on a simulation results analysis. It is identified that OPIM system importance is higher as the number of special processes grows, the demand for quality as the principal product's feature, i.e. as the principal criterion grows, the transportation time and costs fall.